SURGICAL MANAGEMENT OF COMPLETE UTERINE PROLAPSE IN A CAT - Mohamed Shafiuzama; N. Krishnaveni; Mohamed Ali; Gokulakrishnan; Ravi Sundar George (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Uterine prolapse is an eversion of the organ which turns inside out as it passes through the cervix into the vagina. The prolapse can be complete, with both horns protruding from the vulva, or limited to the uterine body and one horn.  A 9 months old Domestic short hair female stray cat was presented with the history of prolapsed uterus through the vulva. Physical examination revealed the cat was dehydrated. Prolapsed uterus was necrotic with laceration and infested with live maggots. The condition was diagnosed as complete uterine prolapse based on clinical observation. The cat was premedicated and induced with xylazine 0.5 mg/kg and ketamine @ 10 mg/kg body weight intramuscularly. Endotracheal intubation was done after topical application of 2% lignocaine. General anaesthesia was maintained with 2% isoflurane with 100% oxygen.  The cat was positioned in sternal recumbency. The live maggots were removed and the dirt and debris were flushed and irrigated with normal saline. A clamp was applied on the prolapsed uterine body, proximal to the clamp ligation was made with PGA 2-0, and the prolapsed uterine portion was amputated distal to the suture and then the proximal portion with ligation were repositioned into the vagina. Cefotaxime @ 20 mg/kg and butorphanol @ 0.2 mg/kg body weight was given intramuscularly for three days follow up. Cat recovered uneventfully.